Menghidupkan Tenggang Rasa: Film Animasi sebagai Kristalisasi Makna Toleransi - Muttaqien, Zaenal (AL-ADYAN, 2022)
Considered as a fresh air by most Indonesians, this article aims to explore the process of identification that occurs when watching animated films. This process can be seen through how animated films play a role in presenting the values presented and how the values are constructed. Furthermore, this article will also review why Indonesian parents want to spend their time watching the animated film series Nussa, especially Nussa: Toleransi (2020). Aired on the Nussa Official youtube channel, there were two groups of viewers who responded to the animated film. First, the audience likes the Islamic values that are presented. Second, the audience did not like the background of the animated film being made. In sum, through animated films, the audience are being asked to be tolerance to others.